Early Postglacial Sedimentation of Lower Seymour Valley, Southwestern British Columbia - Lian, Olav; Hickin, Edward (Géographie physique et Quaternaire, 1996)
In lower Seymour Valley, much of the sediment derived from the erosion of valley-side drift (paraglacial sediments) remains in storage in the form of alluvial fans and aprons. Fluvial incision into these features has exposed sections for lithostratigraphic and chronological study. Radiocarbon dating of organic-rich beds within these deposits indicate that paraglacial sedimentation of lower Seymour Valley commenced before 11.4 ka, was periodic, and was essentially complete by about 9 ka; Seymour River had incised to its present vertical position by about 5 ka. Furthermore, our radiocarbon ages indicate that, although paraglacial sedimentation commenced shortly following deglaciation when the climate was cool and moist, a significant amount of sedimentation occurred during a transition from wet and moist climate to warm and dry (xerothermic) conditions (ca. 10 ka). Charcoal-rich beds indicate that some erosional events may have been a result of slope instability caused by fire.